Deutsche Korpora der internetbasierten und mobilen Kommunikation - Kovbasyuk, L. A.; Ковбасюк, Лариса Анатоліївна; Ковбасюк, Л. А. (Одеса, 2017)
Статтю присвячено німецьким корпусам інтернет-комунікації та мобільної комунікації. Визначено поняття «інтернет-комунікації», «мобільна комунікація», «корпус». Розглянуто теоретичні засади корпусної лінгвістики. Висвітлено найвідоміші корпуси німецької мови інтернет-комунікації та мобільної комунікації, окреслено їхні характерні ознаки.

The article deals with German corpora of Computer-Mediated Communication and of Mobile Communication. The terms "Com-puter-Mediated Communication", "Mobile Communication", "corpus" are defined. The theoretical background of the corpus linguistics is determined. The most important corpora of Computer-Mediated Communication and Mobile Communication are described and their features are analyzed.
Kovbasyuk L. A. Deutsche Korpora der internetbasierten und mobilen Kommunikation / L. A. Kovbasyuk // Одеський лінгвістичний вісник. – 2017. – Вип. 9. – Т.1. – С. 98-102.
Keywords: Research Subject Categories::HUMANITIES and RELIGION; німецька мова; корпус; інтернет-комунікація; мобільна комунікація; German; text corpora; Computer-Mediated Communication; Mobile Communication